2018
DOI: 10.1016/j.jsv.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on in-plane/out-of-plane vortex-induced vibrations of curved cylinder in parallel and perpendicular flows

Abstract: Newcastle University ePrints -eprint.ncl.ac.uk Srinil N, Ma B, Zhang L. Experimental investigation on in-plane/out-of-plane vortex-induced vibrations of curved cylinder in parallel and perpendicular flows. Abstract This study is motivated by an industrial need to better understand the vortex-induced vibration (VIV) of a curved structure subject to current flows with varying directions whose data for model calibration and validation are lacking. In this paper, new experimental investigations on the two-degree-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Since VIV is out of the scope of the present study, interested readers are directed to Refs. [12][13][14] and the relevant references therein.…”
Section: A the Curved Cylinder Wakementioning
confidence: 99%
“…Since VIV is out of the scope of the present study, interested readers are directed to Refs. [12][13][14] and the relevant references therein.…”
Section: A the Curved Cylinder Wakementioning
confidence: 99%
“…In addition to the above-mentioned curved cylinder wake studies, where the cylinder is kept stationary, vortex-induced vibration (VIV) of curved cylinder configurations is also of great interest, motivated by elastic catenary risers. Most VIV studies with curved cylinder configurations are experimental (see de Vecchi, Sherwin & Graham (2009), Srinil (2010), Assi et al (2014) and Srinil, Ma & Zhang (2018), and the studies mentioned therein). Such VIV problems are close to real engineering applications, and the focus of these studies has mainly been on hydrodynamic force coefficients and motions.…”
Section: The Curved Cylinder Wakementioning
confidence: 99%
“…Most VIV studies with curved cylinder configurations are experimental (see de Vecchi, Sherwin & Graham (2009), Srinil (2010), Assi et al. (2014) and Srinil, Ma & Zhang (2018), and the studies mentioned therein). Such VIV problems are close to real engineering applications, and the focus of these studies has mainly been on hydrodynamic force coefficients and motions.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of boundary effect on structure accords with the basic understanding. The oscillation equation (16) can explain the structural response from the angle of single pendulum. The trend can also be used as part of the verification of calculations.…”
Section: Scr Acceleration Response Analysismentioning
confidence: 99%
“…The method is useful for installation issue, and displacement of the top of the riser and underwater tree should be calculated. Narakorn Srinil et al [16] studied vortex-induced vibration at two direction flow velocities in the plane and out of the curved riser and concluded that the maximum (minimum) response occurred in the case of vertical flow. M.M.Cicolin [17] studied the cylindrical vortexinduced response in low mass and damping using the flexible lateral line structure, and the Ventilated Trousers (VT) can make the response reduced by 40% superior compared with other ways.…”
Section: Introductionmentioning
confidence: 99%